KONSEP BUDAYA MEMBACA DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM (Studi Analisis terhadap buku Spiritual Reading karya Raghib As-Sirjani) - Awaliah, Lia Hamdatul; Herlina, N Hani; Munandar, Didih Syakir (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
Reading is an important aspect in the life manusia.Dengan reading could gain knowledge, besides reading is peintah of Allah to all mankind, as contained in Surah al-Alaq paragraph 1-5.Setiap aspect of life involves reading, and in addition the ability to read the guidance reality of everyday human life. Result of this research is the relevance of a culture of reading with the Islamic education was very close relation and comparable straight with the Word of God who first scaled the letter al-Alaq that verses 1-5. Reading is an educational method Illahi.Membaca command in Islam. Read to apply the values ​​of Islamic education in the cultivation of the soul reading culture will deliver the culprit for not doing so except for Allah.